A multi-hysteresis control for minimizing battery charging time within industrial JEITA guidelines - Liang, Rebecca Hui Wen (2023)
In common industrial practices, the Japan Electronics and Information Technology Industries Association (JEITA) guideline is widely adopted for battery temperature regulations. However, the conventional JEITA-compliant temperature-regulated current control (TRCC) is generally designed without considering the charging speed. To address this issue, a multi-hysteresis TRCC (MTRCC) is proposed in this article. The proposed MTRCC is designed based on the conventional JEITA-compliant TRCC by dividing the hysteresis band for each temperature reference from one to multiple. As a result, the number of charging current levels is increased from three to multiple, such that the charging speed can be improved according to the analysis. The proposed control inherits the simple and effective temperature regulations of the conventional control, while enhancing the charging speed without additional hardware costs. This approach has potential to be an alternative of the state-of-the-art TRCC in JEITA guidelines for single-cell charging applications. Empirical results validate that the proposed MTRCC (with four hysteresis bands) can achieve faster charging than the conventional control at four different ambient temperatures and the charging speed improvement is more significant when the ambient temperature is higher.